Two taxonomic rank changes in Pseudognaphalium (Gnaphalieae, Asteraceae) of Mexico - Villarreal Quintanilla, José Ángel; Estrada-Castillón, A. Eduardo; Encina-Domínguez, Juan A. (Instituto de Ecología, A.C., 2020)
Background and Aims: Pseudognaphalium is a genus of the tribe Gnaphalieae (Asteraceae) segregated from Gnaphalium. Since its segregation in 1950, there has been a series of transferences that cover all the Mexican taxa. McVaugh describes Gnaphalium vulcanicum var. monticola and later, Espinosa-García describes G. oxyphyllum var. nataliae. Both names have had nomenclatural changes and, together with the typical varieties, have been kept as infraspecific categories. The purpose of this work was to test if there is support for the recognition as species for each of the four varieties of Pseudognaphalium: P. liebmannii var. liebmannii, P. liebmannii var. monticola, P. oxyphyllum var. oxyphyllum and P. oxyphyllum var. nataliae. Methods: A morphometric analysis was carried out based on the examination of 77 samples and the evaluation of 20 characters, to find the similarity between four infraspecific categories: Pseudognaphalium liebmanii var. liebmannii, P. liebmannii var. monticola, P. oxyphyllum var. oxyphyllum and P. oxyphyllum var. nataliae. Key results: With the use of a multivariate analysis the four studied varieties were objectively differentiated. Each one is an isolated group without overlap among them. Pseudognaphalium oxyphyllum var. nataliae is close to P. oxyphyllum var. oxyphyllum, and P. liebmannii var. monticola appears nearer to P. oxyphyllum var. nataliae than to P. liebmanii var. liebmanii. Conclusions: As a result of the similarity analysis, the separation of the studied varieties allows us to propose Pseudognaphalium monticola and P. nataliae as new taxonomic hierarchies at the species rank.